2017
DOI: 10.1371/journal.pone.0171546
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive procedure reduces adjacent segment degeneration and disease: New benefit-based global meta-analysis

Abstract: ObjectiveAdjacent segment pathology (ASP) is a common complication presenting in patients with axial pain and dysfunction, requiring treatment or follow-up surgery. However, whether minimally invasive surgery (MIS), including MIS transforaminal / posterior lumbar interbody fusion (MIS-TLIF/PLIF) decreases the incidence rate of ASP remains unknown. The aim of this meta-analysis was to compare the incidence rate of ASP in patients undergoing MIS versus open procedures.MethodsThis systematic review was undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
0
12
1
2
Order By: Relevance
“…21 In our study, there was 1 reoperation in the MIS cohort for adjacent segment disease (ASD), compared with 4 reoperations in the open cohort for ASD (1 case) and pseudarthrosis (3 cases). MIS techniques have also been shown to decrease the incidence of ASD following lumbar spine surgeries compared with open approaches because of less soft-tissue disruption, 22 although this conclusion was not observed in our study. During MIS TLIF, when pedicle screws are placed percutaneously, careful attention needs to be paid to avoid iatrogenic superior facet joint violation, which is a known risk factor for ASD.…”
Section: Discussioncontrasting
confidence: 73%
“…21 In our study, there was 1 reoperation in the MIS cohort for adjacent segment disease (ASD), compared with 4 reoperations in the open cohort for ASD (1 case) and pseudarthrosis (3 cases). MIS techniques have also been shown to decrease the incidence of ASD following lumbar spine surgeries compared with open approaches because of less soft-tissue disruption, 22 although this conclusion was not observed in our study. During MIS TLIF, when pedicle screws are placed percutaneously, careful attention needs to be paid to avoid iatrogenic superior facet joint violation, which is a known risk factor for ASD.…”
Section: Discussioncontrasting
confidence: 73%
“…According to the literature about the revision of spinal fusion for the management of ASD, the effective use of minimally invasive surgical transforaminal lumbar interbody fusion (MIS-TLIF) [21] and lateral lumbar interbody fusion (MIS-LLIF) [22] in ASD treatment has been reported. Besides, it has been concluded that MIS-TLIF/PLIF can reduce the incidence rate of ASD, compared with open surgery [23]. Minimally invasive OLIF can be performed safely in the lumbar spine from L1 to L5 and at L5-S1.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that MIS-TLIF is superior to Open-TLIF in reducing adjacent segment disease [34,35]. The smaller damage caused by MIS-TLIF to the surrounding soft tissue and the recovery of postoperative spinal stability may contribute to this difference.…”
Section: Discussionmentioning
confidence: 99%